Smart Antennas in Direction Finding Using Taylor Window - Abhisha Garg; Manisha Khulbe (Scientific Research, New Technologies and Applications Vol. 7, 2024)
A smart antenna (or cognitive antenna or adaptive array) is a self-optimizing intelligent and interactive antenna which can help in the detection of the signal in case of background noise or interference. The major advantage of the Smart Antenna Array includes providing a narrow beam toward the user of interest while nulling the other users who are part of the network. The work includes in designing the Smart Antenna as a transmitter of Uniform Rectangular Array (URA) of Reflector Backed Dipole Antenna (RBDA) placed at Netaji Subhash University of Technology (NSUT), East campus, New Delhi, India. The array is placed at a height of 169 meters above ground level. Each of the RBDA is operating at 10 GHz frequency. The directional finding algorithms not only rely on received signal strength (RSSI) but also depends upon actual direction of the signal which makes the positioning easier. Five receiver locations are selected such that the antenna changes its beam pattern in order to find the maximum receiver placed in the nearby locations using amplitude scanning and steering vector techniques. The results concluded that when Taylor window is used for tapering the beam, the convergence of the algorithm is optimum. The scope future of the work will be in the analysis of Smart Antenna using other more robust adaptive signal processing algorithms and to apply beamforming algorithms instead of beam scanning techniques.